Identification of the first Caledonian A-type granitoids in the southern Qin-Hang belt of south China: Tectonic link to early Paleozoic extension - Liuyun Ouyang; Wenting Huang; Jing Wu; Juan Liao; Jian Zhang; Xilian Chen; Huaying Liang (Solid Earth Sciences, 2023)
Evolution of the late Ordovician–Silurian Caledonian orogeny (ca. 460–420 Ma) in the South China Block (SCB) remains controversial due to the overprinting Triassic (Indosinian) and Jurassic-Cretaceous (Yanshanian) orogenic tectonics and the absence of enough petrologic records. This work reported a systematic study of whole-rock geochemistry, zircon U–Pb geochronology and Hf isotopes of the first Caledonian A-type granitoids (Dishui) in Jinxiu county, Guangxi (SW China). The Dishui granitoids are tectonically located in the southwestern Qin-Hang suture belt, which is the largest ancient orogenic belt formed by the collision of the Yangtze and Cathaysia blocks in South China. The Dishui granitoids consist primarily of a syenogranite pluton with a small-scale granodiorite porphyry dike. The Dishui syenogranite and granodiorite porphyry have LA-ICP-MS zircon U–Pb ages of 437.9 ± 1.0 Ma (MSWD = 0.77) and 436.6 ± 0.8 Ma (MSWD = 1.7), respectively. The syenogranite has high contents of SiO2 (73.20–77.35 wt.%), total alkalis (Na2O + K2O = 7.42–8.99 wt.%), total REE (198–445 ppm), high field strength elements (HFSEs: Zr + Nb + Ce + Y = 253–520 ppm), and 10,000∗Ga/Al (2.93–3.11) and FeOt/(FeOt + MgO) (0.77–0.96) ratios and high F concentration, resembling highly-fractionated A-type granite. The granodiorite porphyry displays similar A-type granite affinities, including high (Zr + Nb + Ce + Y) (410–485 ppm), 10,000∗Ga/Al (2.47–4.59), and zircon saturation temperature (TZr = 908–927 °C), medium to high SiO2 (64.56–64.95 wt.%), Fe2O3 (7.70–8.11 wt.%), and MgO (3.69–4.09 wt.%), and low FeOt/(FeOt + MgO) (0.61–0.64), resembling magnesian unfractionated A-type granitoid. The Dishui syenogranite and granodiorite porphyry dike have zircon εHf(t) value and two-stage model age (TDM2) of −3.9 to +1.5 and 1.32–1.66 Ga, and −1.7 to +11.8 and 0.94–1.53 Ga, respectively, both much more depleted than many Caledonian gneissic/massive granites and the Devonian A-type granites (εHf(t) = −14.9 to −3.5) in South China. All these data suggest that the Dishui syenogranite was derived from partial melting of the Proterozoic metamorphic basement with mantle-derived melt input, and the magma subsequently underwent extensive fractionation. Meanwhile, the Dishui granodiorite porphyry was likely derived from the same crustal melt with more mantle-derived input. New ages of the Dishui A-type granitoids (ca. 436–437 Ma) in the Qin-Hang belt indicate a tectonic transition from syn-collisional crustal thickening to post-collisional extension at ∼437 Ma in South China.